PERLINDUNGAN HUKUM KORBAN PENCURIAN DATA PRIBADI (PHISHING CYBERCRIME) DALAM PERSPEKTIF KRIMINOLOGI - Akbar Galih Hariyono; Frans Simangunsong (Gapenas Publisher, 2023)
Phishing Cybercrime is a crime of criminal acts committed on internet technology (cyber space), both attacking public facilities and private facilities. crime Phishing cyber is an unlawful act committed using the internet based on the sophistication of computer and telecommunications technology. Activities Phishing cybercrime can be carried out at any location or even between countries. crimes Phishing cybercrimes such as hacking, sharing personal information and counterfeiting credit cards. Actors Phishing themselves are called hackers. Hackers have the knowledge and ability to master and apply programming languages. This ability is obtained hackers in various ways, including by learning from experts or self-taught. In a criminological perspective, phishing cybercrime occur because of 2 (two) important factors, namely Technical Factors and Economic Factors which can cause phishing cybercrime to occur. Legal protection regarding cybercrime phishing has been regulated in the ITE Law and the Personal Data Protection Law. Phishing cybercrime still cannot be completely eliminated. The existence of this law can at least reduce the amount of cybercrime in Indonesia